Venture Capitalism, High-Technology Financing and the State's Innovation Policy: A Sociological Analysis of the U.S. Experience (1940s-2010s) - Dmitrii Zhikharevich (Journal of Economic Sociology, 2021)
This paper reviews the theoretical and research literature on venture capi¬talism. The major approaches to the study of venture financing and its institutional forms are considered against the background of the experi¬ence of the U.S., where this industry exists the longest. Economists ana¬lyze venture capital as an institutional response either to the failure of the market for knowledge or to the failure of the market for entrepreneurial finance. Economic sociologists complement this analysis by emphasiz¬ing venture capital firms' role in socializing technological entrepreneurs, indirect financing of innovation ecosystems, and risk management. In the more recent literature inspired by critical political economy and economic history, this functionalist, market-failure type of argument is increasingly called into question because of its insufficient attention to the role of the state in creating and maintaining the venture capital industry. Based on this literature, the paper illustrates the connection between the genesis of the venture capital industry in the U.S. and the evolution of the devel¬opmental state in post-war U.S. In conclusion, this paper discusses insti¬tutional alternatives to venture capital and the applicability of the U.S. experience to other contexts.